Studi Explorasi Permasalahan Kesehatan di Desa Pesaren Kecamatan Warungasem Kabupaten Batang Melalui Pendekatan Community Needs Diagnosis - Rr. Vita Nur Latif; Nor Istiqomah (Universitas Pekalongan, 2013)
Background : Community empowerment requires the independence efforts of society, and sensitizing the community itself is expected to recognize and identify the problems that exist in the community, especially health problems. The essence of community empowerment through community needs diagnosis effort is able to independently identify, exemine issues, prioritize problems, make a plan of intervention based on issues as resolving disputes. This is what underlies the implementation of this research entitled Explorations of Health Problems in Pesaren, Kecamatan Warungasem, District of Batang through Community Needs diagnosis approach. Methods : The study using a qualitative case study approach. The collection of data through observation, in- depth interviews and FGD (Focus Group Discussion) to explore health issues through community needs diagnosis. Informants of this study consisted of elements of community leaders, head of the health center and village midwives related. Results : Based on the results of the study identified several health problems in Pesaren subdistrict Warungasem Batang is scabies, Acute respiratory tract infections (ISPA), dermatitis, cephalgia, Diarrhea. Based on Hanlon mathematical calculation, scabies is a priority issue that must be resolved, by a score of 600. This calculation is based on severity of problems (severity), the number of people affected (prevalence), the increase in disease rate (rate of increase), community desire (degree of unmeet needs), social advantages if the problem is resolved (social benefits), community concerns about the issue (public concern), the availability of technology (technical feasibility), the resources (resources availability), and political support (political climate). Keywords : health issues, community needs diagnosis